RETRACTED: Toward tailored exosomes$bthe exosomal tetraspanin web contributes to target cell selection - Rana, Sanyukta; Yue, Shijing; Stadel, Daniela; Zöller, Margot (International journal of biochemistry & cell biology, 2012)
This article has been retracted: please see Elsevier policy on Article Correction, Retraction and Removal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal). Post-publication, an investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team identified a concern around the authenticity of the following figures/image panels: Analysis verified with high confidence, the blot duplication posted on PubPeer; with additional instances of blot splicing. • Figure 1A - the CD151 and neuropilin blots are identical • Figure 1B - in the 'antiCD49c' IP blots, the tspan8 row has a clear line where the control lane has been spliced into the blot • Figure 1C - in the 'GDF15' IP blots, the CD9 row has a clear line where both the control lane and the AS-tspan8 lane have been spliced into the blot The authors were requested to provide comment on these concerns, as well as the original unprocessed image files to aid investigation. The explanation provided was unsatisfactory in resolving these concerns. The Editor-in-Chief has determined that the findings of the article cannot be relied upon, and has decided to retract the article.
Online verfügbar: 19. Juni 2012
Gesehen am 12.01.2026